Acehnese Cultural Leaders' Perspective on Anemia in Pregnant Women: A Qualitative Study. (9th June 2020) - Darmawati, Darmawati; Siregar, Tongku N.; Kamil, Hajjul; Tahlil, Teuku
Abstract : Introduction . Anemia during pregnancy is one of the commonest issues in pregnancy. Cultural belief is among the contributing factors to this problem. This study aims to explore the cultural leaders' perception on Acehnese culture regarding anemia in pregnancy. Methods . The qualitative study was conducted using three in-depth interviews and a focus group discussion with Acehnese cultural leaders. Data analysis was conducted by the inductive content analysis method. Results . Four themes emerged from interviews and discussion: (1) cultural beliefs about anemia; (2) locally resourced food; (3) husband participation in preventing anemia during pregnancy; (4) do's and don'ts. Conclusion . Our findings provide insight into how cultural leaders' perceptions of anemia are in pregnancy and how they are integrated strongly into Acehnese people's lives. These findings would assist in developing culturally adapted strategic policy to prevent anemia during pregnancy.